Respuesta :
Let's solve the equation!
3(x - 5) - 12 = 2(x - 6) + 2
Use the distributive property, which states: a(b-c) = ab - ac
3x - 3(5) - 12 = 2x - 2(6) + 2
3x - 15 - 12 = 2x - 12 + 2
3x - 27 = 2x - 10
Subtract 2x on both sides
x - 27 = -10
Add 27 on both sides.
x = 17
When x = 17, the equation 3(x - 5) - 12 = 2(x - 6) + 2 is true.
3(x - 5) - 12 = 2(x - 6) + 2
Use the distributive property, which states: a(b-c) = ab - ac
3x - 3(5) - 12 = 2x - 2(6) + 2
3x - 15 - 12 = 2x - 12 + 2
3x - 27 = 2x - 10
Subtract 2x on both sides
x - 27 = -10
Add 27 on both sides.
x = 17
When x = 17, the equation 3(x - 5) - 12 = 2(x - 6) + 2 is true.
3(x - 5) - 12 = 2(x - 6) + 2
3x - 15 - 12 = 2x - 12 + 2
3x - 27 = 2x - 10
-2x -2x
x - 27 = -10
+27 +27
x = 17
Answer: the value of x is 17
3x - 15 - 12 = 2x - 12 + 2
3x - 27 = 2x - 10
-2x -2x
x - 27 = -10
+27 +27
x = 17
Answer: the value of x is 17